(untitled) (Journal of Universal Science Research, 2026)
This study explores developmentally appropriate and evidence-based methods for teaching English to preschool-aged children, with an emphasis on listening comprehension, multimodal learning, and play-based instruction. Preschool learners aged 4–6 process language through imitation, sensory experience, and emotional engagement rather than through analytical reasoning or grammar-based approaches. Using a qualitative descriptive-analytical methodology, the study examines the effectiveness of Total Physical Response (TPR), multimodal materials, storytelling, songs, and play-centered techniques commonly used in early childhood education worldwide. Results demonstrate that preschool children acquire vocabulary, understand simple verbal instructions, and develop early communicative abilities more effectively in environments that emphasize movement, meaningful repetition, and multimodal input. The discussion highlights implications for educators and curriculum designers, emphasizing the need for short, dynamic lessons that incorporate sensory, emotional, and physical experiences. The study concludes that child-centered, play-based English instruction significantly enhances motivation, comprehension, and long-term retention among preschool children.